Oral History Interview: Earl F. Smith - Smith, Earl F.
Born in Dubuque, Iowa in 1901, Smith came out to California in 1954. As a salesman, he traveled through states affected by the Dust Bowl and saw the "tin can tourists" moving west. Smith describes the conditions just before the Dust Bowl in Kansas and the mechanization of farm work. He claims the Great Depression did not occur overnight, but progressed westward with small farmers losing their land until the economy stabilized around in 1935. Smith portrays how the New Deal programs provided work. He provides a vivid description of the dust storms.